PENGARUH KUALIFIKASI AKADEMIK DAN MOTIVASI BERPRESTASI TERHADAP PROFESIONALISME GURU TK MELALUI IKLIM SEKOLAH SEBAGAI VARIABEL INTERVENING DI KECAMATAN RANCASARI KOTA BANDUNG - Kansil, Imelda Christine; Hardian, Dafyar Eliadi; Firdaus, Muhammad Yus (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the influence of academic qualifications and achievement motivation on the professionalism of kindergarten (TK) teachers in Rancasari District, Bandung City, with school climate as an intervening variable. The study used a quantitative approach with an ex post facto design and Structural Equation Modeling (SEM) analysis based on Partial Least Squares (PLS). The subjects were kindergarten teachers in Rancasari District, with data collected through a questionnaire measuring academic qualifications, achievement motivation, school climate, and teacher professionalism. The results showed that (1) academic qualifications significantly influence kindergarten teacher professionalism; (2) achievement motivation significantly influences kindergarten teacher professionalism; (3) school climate does not have a direct significant effect on teacher professionalism but plays a significant role as a mediating variable in the relationship between academic qualifications and teacher professionalism; (4) academic qualifications and achievement motivation significantly influence school climate; and (5) school climate significantly mediates the relationship between achievement motivation and teacher professionalism. These findings confirm that improving teachers' academic qualifications and achievement motivation, supported by a conducive school climate, can enhance the professionalism of kindergarten teachers. Practical implications: Early Childhood Education (PAUD) administrators need to create a supportive and collaborative work environment, while education policies should focus on improving academic qualifications and fostering teacher motivation systematically. Keywords: Academic Qualifications, Achievement Motivation, School Climate, Teacher Professionalism, Early Childhood Education.